Producto audiovisual sobre la evolución del sonido en el cine ecuatoriano. - Gómez Bracho, Carlos Esteban (2018)
The importance of the sound in the cinema, with the passage of the time, goes in increase due to his sophistication. After the success that had the silent cinema worldwide, the evolution at visual and sonorous level allowed it to be positioned as a magisterial industry, which, nowadays it is capable of stablish cultural structures and it has become part of the world pop and it serves as a record data of the history. The Ecuadorian cinema, bearing in mind that initiated with a technological delay, has a golden epoch in the production of the silent cinema, despite that worldwide was already having the premiere of sonorous cinema. In our country, the music that was interpreted in the live cinema as the first attempts of recording the sound in Ecuadorian movies forms a part of an audiovisual identity which has not lasted along the history because many film treasures from 1911 to 1940 have been lost over the years. It is known that the set of the music in the films had a very educated aspect; however, the national music started to be more representative than the conventional music that the cinema usually presents.